Edukasi Green Chemistry: Daur Ulang Minyak Jelantah menjadi Sabun sebagai Upaya Pengurangan Limbah Rumah Tangga: Green Chemistry Education: Recycling Used Cooking Oil into Soap as an Effort to Reduce Household Waste - Novrianti, Novrianti; Purnamawati, Neneng; Anggreana, Vella; Alwiah, Sy. Sarah; Harmiyati, Harmiyati; Mildawati, Roza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The increasing household consumption of cooking oil has led to a rise in used cooking oil waste, which, if reused, can endanger health and, if disposed of carelessly, causes environmental pollution. This condition prompted the implementation of a community service program, which involved training women's religious study groups in Bumi Sejahtera Housing, Pekanbaru City, on how to use cooking oil in soap. This activity aimed to enhance community knowledge about the dangers of using used cooking oil, raise environmental awareness, and provide practical skills in processing used cooking oil into soap products that have both functional and economic value. The program was conducted in several stages, including a preliminary survey, material preparation, socialization, soap-making demonstrations, hands-on practice with participants, and post-training evaluation. The results showed high enthusiasm from participants, as reflected in their active involvement during discussions and practical sessions. Participants could produce soap from used cooking oil with good foaming quality and fragrance, making it suitable for household use. In addition, some participants expressed interest in continuing independent soap production by collecting used cooking oil from the surrounding community, thereby opening up opportunities for program sustainability and increasing the economic value of household waste. This program successfully improved community understanding of the impacts of used cooking oil, reduced potential environmental pollution, and provided skills that can be further developed into small-scale businesses.